(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
In this scientific work, the need to improve investment mechanisms in ensuring financial stability in small businesses. The study stipulates the role of investments in stabilizing the financial condition of small businesses, effective methods of attracting them, as well as available problems. In the national economic situation, it will also offer ways to develop small businesses through the improvement of investment activity, foreign and local investors. As a result of the work, proposals and recommendations for small businesses have been developed.